Resilience and pastoralism in Africa south of the Sahara, with a particular focus on the Horn of Africa and the Sahel, West Africa - Little, Peter D.; McPeak, John G. (International Food Policy Research Institute, 2014)
Recently there has been a great deal of interest in applying the concept of resilience to pastoral systems and to development programs in pastoral systems. This paper addresses pastoralism and its resilience in Africa south of the Sahara, with a primary focus on the Horn of Africa and some contrast to West African examples. It begins with an overview of the realities of contemporary pastoralism in this area that highlights social, economic, and political challenges and opportunities. It then focuses on the concept of resilience and its applications in the specific context of pastoral production systems. After discussing the general appeal of resilience for analyzing these systems, the paper illustrates specific elements of pastoralism that enhance or constrain household‐level resilience. Empirical